Oncology palliative care: trends of the scientific production - Araújo, Daiana de (2011)
This study aims to identify trends in scientific literature about the topic of oncology palliative care to review what’s current in the topic. It was constructed by integrative literature review conducted through the electronic search in the Virtual Health Library - VHL in database American and Caribbean Literature in Health Sciences - LILACS Scientific Electronic Library - SCIELO and International Literature in Health Sciences - MEDLINE. Data were grouped into four themes: ethical issues in palliative care, the impact of the terminally ill individual's life, the quality of life in palliative care and palliative home care. Through this, the discussion of the concept of palliative care in oncology and complex issues involving the theme is preceded, ethics and death also appears. However, the health system and professionals to discuss are pointed, such as the implement policies and health services for terminal patients care